Potensi Pengembangan Tanaman Lada (Piper nigrum L) Pada Wilayah Kecamatan Muara Badak - Akhmad Sopian; Zainudin Zainudin (Universitas Widya Gama Mahakam, 2018)
Farmers generally plant pepper on ultisol soil. Ultisol soil is classified as acid mineral soil which has a wide distribution, but has the potential to develop agricultural land including pepper plantations. The tendency of land used for agricultural activities shows a decrease in soil fertility, indicated by the occurrence of erosion, imbalance of nutrients present in the soil and stronger soil dependence on fertilizer, as well as lower crop production. The research aims to find out the characteristics of pepper land, productivity, potential land for the development of pepper plants in Muara Badak District. This research was carried out using survey methods with stages including; overlaying land maps, interviews, secondary data inventory, in the form of data on the number of farmers, land area, production and cultivation techniques, and analysis of soil samples in the laboratory. The results showed that the population / ha of pepper plants was different for each farmer, where the spacing was 110 x 110 cm, 120 x 120 cm, 130 x 130 cm and 140 x 140 cm with a population between 1300 - 4500 staples / ha. Farmers generally use lodrin organic fertilizer, but are not carried out intensively, and the land management system does not pay attention to the aspect of soil conservation, farmers' land has been cultivated for generations without using terraces and soil cover. The tendency of nutrient loss on the land is quite high because the land is located on a hill and is quite steep at 16-40% slope. Pepper productivity in the study area is quite high, with an average of 1,437 kg / ha. The highest productivity in Salo Palai village reached 1970 kg / ha, while the lowest in Batu Batu village was 830 kg / ha. The results of soil analysis in the two study locations that the content of the element N was classified as medium, the total K was classified as high to very high. pH and CEC are low, this can affect nutrient absorption, so that lime is needed and the addition of organic matter if fertilization is carried out.